Efektivitas Sanksi Pidana dalam Meningkatkan Kepatuhan Wajib Pajak: Analisis dalam Perspektif Ekonomi Perpajakan - Santi Suryani; Muhamad Reza Atqia; Sandra Leoni Prakasa Yakub; Fitri Ajeng Sari; Novia Laela (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
This study aims to analyze the effectiveness of criminal sanctions in improving taxpayer compliance in Indonesia from a tax economics perspective, and to identify factors influencing this effectiveness. This research uses a normative juridical approach supported by limited empirical analysis through an examination of legislation, legal theory, and secondary data related to tax compliance and enforcement. The findings indicate that criminal sanctions function as a repressive and preventive instrument in the tax system; however, their effectiveness remains suboptimal. This condition is caused by the low probability of tax audits, the complexity of law enforcement, and the dominance of an administrative approach that places criminal sanctions as a last resort. Furthermore, taxpayer compliance is influenced not only by the threat of sanctions but also by moral considerations, the level of trust in the government, and the perception of the fairness of the tax system. Theoretically, the effectiveness of criminal sanctions is determined by the interaction between law enforcement strength, administrative capacity, and taxpayer trust. Therefore, a more comprehensive policy approach is needed through the integration of criminal and non-criminal instruments to sustainably improve taxpayer compliance.